MicroRNA signatures in plasma and plasma exosome during window of implantation for implantation failure following in-vitro fertilization and embryo transfer - Hong Zeng; Yu Fu; Lang Shen; Song Quan (BMC, 2021)
Abstract Background MicroRNAs (miRNAs) are small, non-coding RNAs that are dysregulated in many diseases and can act as biomarkers. Although well-studied in cancer, the role of miRNAs in embryo implantation is poorly understood. Approximately 70% of embryos fail to implant following in-vitro fertilization and embryo transfer, 10% of patients experienced recurrent implantation failure. However, there are no well-established biomarkers that can predict implantation failure. Our purpose is to investigate distinct miRNA profiles in plasma and plasma exosomes during the window of implantation between patients with failed implantation and successful implantation. Methods We select a nested case-control population of 12 patients with implantation failure or successfully clinical pregnancy using propensity score matching. RNA was extracted from plasma and plasma exosomes collected during the window of implantation (WOI). MicroRNA expression in all samples was quantified using microRNA sequencing. The intersection of differently expressed miRNAs in plasma and exosomes were further validated in the GEO dataset. Significantly altered microRNAs in both plasma and plasma exosomes were then subjected to target prediction and KEGG pathway enrichment analyses to search for key signaling pathways. WGCNA analysis was performed to identify hub miRNAs associated with implantation. Results 13 miRNAs were differentially expressed in both plasma and plasma exosomes in patients with implantation failure. Among them, miR-150-5p, miR-150-3p, miR-149-5p, and miR-146b-3p had consistent direction changes in endometrium of patients with recurrent implantation failure (RIF), miR-342-3p had consistent direction changes in blood samples of patients with RIF. Pathway enrichment analysis showed that the target genes of differentially expressed miRNAs are enriched in pathways related to embryo implantation. WGCNA analysis indicated that miR-150-5p, miR-150-3p, miR-146b-3p, and miR-342-3p are hub miRNAs. Conclusions Implantation failure is associated with distinct miRNA profiles in plasma and plasma exosomes during WOI.